Aspek hukum kontrak dagang via internet (cyberspace transactions) dalam perspektif sistem hukum Islam - Wijayanto Setiawan (State Institute of Islamic Studies (IAIN) Salatiga, 2010)
Trade contracts via the internet (cyberspace transactions) or e-commerce or in other terms is a necessity inthe development of cyberspace in the last ten decades. In terms of the applicable legal aspects, contractstrade via the internet is having a substantial difference with the conventional contract law. From theviewpoint of Islamic Law (fiqh), the implementation of e-commerce business transactions can besamed with al-salam transactions in the way of payment and delivery of commodities which serve as theobject of the transaction. Transactions in e-commerce over the Internet can be aligned with the principlesof the existing transaction in the transaction al-salam, especially relating to the parties involved in thetransaction, the consensus statement and transaction through a transaction object. Based on thesestudies, the commercial transactions over the Internet is allowed as long as meet the principles of thecontract (‘aqad) in Islam, namely: (1) the parties involved in implementing the contract with proves goodand sincerity; (2) the process of conveying statements of the consensus between party is clear and notconflicting with shar’i; and (3) the object of transactions (goods or services) is something that is halal.